Starter home : discovering the past in central New York - Svenson, Peter (Algora Publishing, 2017)
"Fayetteville grew from a late-18th century crossroads in the central New York wilderness to a fully industrialized 19th century community, thanks to the nearby Erie Canal. Today it is a bedroom suburb east of Syracuse. Svenson's treatment of the village's historical perspective is interspersed with a description of his own experience in moving there - factual history leavened by present-day description."--Provided by customer.